1984
DOI: 10.1136/bjo.68.11.811
|View full text |Cite
|
Sign up to set email alerts
|

Immune complexes in retinitis pigmentosa.

Abstract: SUMMARY In a group of 46 patients with retinitis pigmentosa (RP) we studied the presence of circulating immune complexes (CIC) and the alterations in the complement system. Our results showed the presence of CIC in 43.5% of the patients studied, reduced levels of the complement components C3 and C4 (p<0-001), and of the haemolytic activity CH50 (p<0-001) when compared with a control group consisting of a 100 healthy subjects. We found a statistically significant correlation between the values of C3 and CIC (p<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…A recent transcriptome study of two advanced stages of RP in dogs showed strongly increased gene expression of inflammasome and complement factors in the retina (Sudharsan et al, 2017). However, earlier studies reported reduced C3 and C4 levels and increased immune complexes in the sera from RP patients, and this reduced systemic complement activity appears to be related to poor disease prognosis (Heredia et al, 1984). The rhodopsin T17M mutation also reduces C3 secretion in RPE cells (Xiong et al, 2017), suggesting that some RP-related genes may regulate complement expression/secretion by RPE cells.…”
Section: The Role Of the Complement System In Retinal Degenerationmentioning
confidence: 98%
“…A recent transcriptome study of two advanced stages of RP in dogs showed strongly increased gene expression of inflammasome and complement factors in the retina (Sudharsan et al, 2017). However, earlier studies reported reduced C3 and C4 levels and increased immune complexes in the sera from RP patients, and this reduced systemic complement activity appears to be related to poor disease prognosis (Heredia et al, 1984). The rhodopsin T17M mutation also reduces C3 secretion in RPE cells (Xiong et al, 2017), suggesting that some RP-related genes may regulate complement expression/secretion by RPE cells.…”
Section: The Role Of the Complement System In Retinal Degenerationmentioning
confidence: 98%
“…However, results have been complicated by the fact that immune reactivity appears to vary amongst RP patients possibly reflecting the genetic heterogeneity of the disease. Studies suggested that circulating immune complexes could be detected in less than 50% of RP patients [50]. This was, however, reported as significant since it correlated with statistically significant reductions of circulating complement factors C3 and C4 and a significant reduction in time taken for RP patient sera to achieve 50% hemolysis of sheep red blood cells [50].…”
Section: Established Links Between Inflammation and Genetic Retinamentioning
confidence: 99%
“…Studies suggested that circulating immune complexes could be detected in less than 50% of RP patients [50]. This was, however, reported as significant since it correlated with statistically significant reductions of circulating complement factors C3 and C4 and a significant reduction in time taken for RP patient sera to achieve 50% hemolysis of sheep red blood cells [50]. A link with HLA status has also been reported in RP patients [51], and vitreous samples from RP patients have been shown to contain many immune system cells such as various types of lymphocytes [52].…”
Section: Established Links Between Inflammation and Genetic Retinamentioning
confidence: 99%
“…C1q and C3 are involved in synapse elimination as shown by the failure of C1q-and C3-deficient mice to fully refine retinogeniculate connections during postnatal development [Stevens et al, 2007;Stephan et al, 2013]. In addition, clinical evidence showed that C3 level was significantly decreased in RP patients compared to control [Heredia et al, 1984]. It was suggested that the protective effect of C3 may be related to the role of C1q and C3 in the clearance of apoptotic cells from the retina [Humphries et al, 2012].…”
Section: Discussionmentioning
confidence: 99%
“…C3 plays dual role in different retinal degeneration diseases [Heredia et al, 1984;Cashman et al, 2011]. Reduced levels of complement components C3 and C4 were observed in patients with RP [Heredia et al, 1984]. C3 is expressed in the retinal and RPE/ choroidal tissues, as well as in cultured RPE [Yang et al, 2009;Luo et al, 2011;Luo et al, 2013].…”
mentioning
confidence: 99%